Love of Money, Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence Influence Students Perceptions of Accounting Professional Ethics: Case Study of Accounting Students at Panca Budi Development University and the University of North Sumatra - Daning Indah Lestari; Vina Arnita (Proceeding of The International Conference on Business and Economics, 2025)
This study aims to analyze the influence of Love of Money, Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence Influence Students Perceptions of Accounting Professional Ethics. The objects of this study are students of the Accounting study program from Panca Budi Development University and the University of North Sumatra. This study uses a quantitative approach with an associative research type. The research population consists of students from the 2020 to 2022 intake with a total of 1,647 people, including 467 students from Panca Budi Development University and 1,180 students from the University of North Sumatra. The sample was determined using the Slovin formula, so that 94 respondents were obtained as research samples. The data used consists of primary and secondary data. Primary data was collected by distributing questionnaires to respondents, while secondary data was obtained from various sources such as reports, books, documents, and relevant scientific publications. Data analysis was carried out using SPSS software version 25. Analysis techniques include descriptive statistical analysis, validity and reliability tests, and classical assumption tests that include normality, multicollinearity, and heteroscedasticity. Furthermore, multiple linear regression analysis was conducted and hypothesis testing was carried out using the t-test and coefficient of determination (R²). The results of the study indicate that partially, the variables Love of Money, Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence have a positive and significant Influence Students Perceptions of Accounting Professional Ethics.